Raindrop size distribution variability associated with size‐dependent advection in convective precipitation systems - Megumi Okazaki; Kosei Yamaguchi; Tomoro Yanase; Eiichi Nakakita (Atmospheric Science Letters)
Abstract Raindrop size distribution (DSD) is fundamental for understanding precipitation processes. This study utilized a two‐dimensional simulation with bin cloud microphysics parameterizations to investigate the spatiotemporal variability of DSDs owing to the influence of mesoscale circulation associated with the precipitation system. The simulated multicellular convection went through developing, mature, and dissipating stages, with updraft weakening and rainfall area expanding through these stages. The width of the DSD narrowed as rainfall weakened. In addition, a significant bimodal DSD was observed during the dissipating stage. Furthermore, we investigated the spatial distribution of the number density of raindrops corresponding to the maximum, local minimum, and local maximum of the significant bimodal DSD in the dissipating stage. According to the results, the raindrops constituting the maximum, local minimum, and local maximum followed different advection processes. This size‐dependent advection effect may have contributed to the bimodal DSD formation.